(untitled) (KYAMC Journal, 2017)
Title: Role of computed tomography in the evaluation of severity of acute pancreatitis. Introduction: Early diagnosis and determination of severity of acute pancreatitis is important for management and it depends largely on severity of disease. Medical treatment of mild acute pancreatitis includes conservative management while severe acute pancreatitis requires intensive care to surgical intervention (open or minimally invasive) in selected cases. Methodology: This prospective study was carried out to find out the correlation between modified CT severity index and patient’s clinical outcome in acute pancreatitis enrolling 96 subjects in the department of Radiology and Imaging, BIRDEM during two years time period. Severity of acute pancreatitis was assessed by both clinical and imaging staging (Modified CT severity index) in mild, moderate and severe groups. Result: Mean age ( ± SD) of the study subjects was 35.48 ± 14.59 years and number of male was 60 (62.50%) and female was 36 (37.50%). Acute pancreatitis was associated with hypertriglyceridemia (19.79%), gall stone (12.5%), post ERCP (6.25%) and alcoholism (2.08%). Aetiology was unidentified in 59.73% subjects. Majority of the subjects with acute pancreatitis presented with abdominal pain, fever (20.08%), vomiting (54.41%) and oedema (25%). On imaging, diffuse pancreatic enlargement was noted in 29.16% subjects. Pancreatic inflammation with and without peripancreatic fat involvement were observed in 27.08% and 72.91% subjects respectively. Pseudocyst formation (13.54%), ascites (30.20%), renal fascia involvement (46.87%) and pleural effusion (37.5%) were seen in CT scan. Severity of acute pancreatitis was evaluated by clinical findings and CT severity index and the measure of agreement between clinical and imaging staging was almost perfect. CT severity index in acute pancreatitis had statically significant relation with clinical outcome (0.573), organ failure (0.674), need for surgical intervention (0.463) and hospital stay (0.235). Conclusion: Modified CT severity index in acute pancreatitis correlates with patient outcome. During reporting if this simple scoring system is applied then we can easily measure the severity and determine whether patient need medical or surgical intervention. KYAMC Journal Vol. 7, No.-2, Jan 2017, Page 738-744